2018
DOI: 10.3389/fnhum.2018.00155
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of Long-Term Potentiation-Like Activity in the Dorsolateral Prefrontal Cortex

Abstract: Background: Long-term potentiation (LTP) depends on glutamatergic neurotransmission and is modulated by cholinergic, dopaminergic and GABAergic inputs. Paired associative stimulation (PAS) is a neurostimulation paradigm that, when combined with electroencephalography (EEG), assesses LTP-like activity (PAS-induced LTP) in the dorsolateral prefrontal cortex (DLPFC). Thus, we conducted a study to assess the role of cholinergic, dopaminergic, GABAergic and glutamatergic neurotransmission on PAS-induced LTP in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Specifically, five articles examined SICI, 21,45,[79][80][81]110 13 articles studied LICI, [42][43][44][82][83][84][85][86][87]103,104,108,111 four articles investigated SAI, 46,53,88,89 three articles investigated ICF, 21,45,81 and five articles investigated PAS. [90][91][92][93]109 Additionally, 11 articles examined the pharmacological effects on TEP 80,[101][102][103][104][105][106][107][108][109][110] and eight articles studied technical aspects of TMS-EEG analyses (e.g., artifact reduction). 16,111,[113][114][115][116]124,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, five articles examined SICI, 21,45,[79][80][81]110 13 articles studied LICI, [42][43][44][82][83][84][85][86][87]103,104,108,111 four articles investigated SAI, 46,53,88,89 three articles investigated ICF, 21,45,81 and five articles investigated PAS. [90][91][92][93]109 Additionally, 11 articles examined the pharmacological effects on TEP 80,[101][102][103][104][105][106][107][108][109][110] and eight articles studied technical aspects of TMS-EEG analyses (e.g., artifact reduction). 16,111,[113][114][115][116]124,…”
Section: Resultsmentioning
confidence: 99%
“…Dextromethorphan (NMDA receptor antagonist) and levodopa (L-DOPA) did not change the DLPFC TEP of LICI compared to placebo. 109 Furthermore, Salavati et al performed a PAS paradigm on the DLPFC five times in a random order, each preceded by the administration of placebo or one of four active drugs, in a randomized controlled, doubleblind, crossover study. PAS-induced LTP was examined following the administration of each drug and compared with PAS-induced LTP after placebo.…”
Section: Other Neurotransmissionsmentioning
confidence: 99%
“…The neurophysiological substrates of the dlPFC-PAS were further investigated by Salavati et al (2018). Considering that synaptic LTP depends on glutamatergic neurotransmission and is modulated by cholinergic, dopaminergic, and GABAergic neurotransmission (Malenka and Bear, 2004).…”
Section: Neuroplasticity Induction In Frontal Networkmentioning
confidence: 99%
“…Considering that synaptic LTP depends on glutamatergic neurotransmission and is modulated by cholinergic, dopaminergic, and GABAergic neurotransmission (Malenka and Bear, 2004). Salavati et al (2018) investigate whether drugs influencing these neurotransmitters could modulate the effects of the dlPFC-PAS. Results showed that PAS after-effects (i.e., dlPFC-TEPs) are enhanced by L-DOPA and rivastigmine; these two drugs increase dopaminergic and cholinergic tone.…”
Section: Neuroplasticity Induction In Frontal Networkmentioning
confidence: 99%
See 1 more Smart Citation